Penerapan Pemilihan Maskapai Penerbangan Untuk Komoditas Perishable Cargo Tujuan Singapore Pada Jasa Freight Forwarding Menggunakan Metode AHP-TOPSIS - Himawan, Raka; Rosandi, Iwan (Universitas Mercu Buana, 2020)
PT. Global Trans Maju Empat Empat is one of the freight forwarding in Indonesia has several airline vendors to supply perishable commodity demand to Singapore with several criteria. Errors in the selection of aviation vendors have an impact on productivity and operations. To determine the priority level of the criteria, the Analytical Hierarchy Process ( AHP ) method was used and combined with the topsis brainstorming results obtained by the Facility criteria with the Cool Room Sub criteria as a prerequisite for pre-qualification for the smooth process of shipping perishable cargo to Singapore. Furthermore, based on the calculation of AHP sub criteria price Range (0.602), Cool Room (0.588), Direct Flight (0.520), and CS performance (0.529) into sub criteria with the largest weight sequentially and at level three, namely alternative calculation based on AHP and TOPSIS obtained by Garuda Airline (A1) of (0.291) (0.664), Air Asia (E5) of (0.229) (0.645), Singapore 0.190) (0.491), Myindo Airlines (C3) amounted to (0.164) (0.531), Malaysia Airlines (D4) amounted to (0.087) (0.445). the best priority weight is obtained by Garuda Airlines (A1) and becomes the airline vendor recommendation to transport perishable cargo to Singapore.